Attempting to Transform the Mental Landscape of the Indian 'Heathen' in Mary Sherwood's The Indian Pilgrim (1818). (22nd February 2017) - Malhotra, Ashok
Abstract: This article focuses on Mary Sherwood's Christian catechetical narrative The Indian Pilgrim (1818). It proposes that the narrative needs to be contextualised in relation to the author's involvement in Anglican Evangelical proselytising activities within the subcontinent in the early nineteenth century. A textual analysis of the narrative, combined with an investigation of the circumstances in which it was produced, reveals that the narrative aimed to condition Indian readers into being obedient Christian subjects who recognised their supposed dependence on their white sahibs or memsahibs. It also highlights the stratagems by which the author attempts to coerce them into accepting the primacy of the written text as the ultimate repository of spiritual truth. The argument demonstrates the ways in which Hinduism was viewed by evangelicals as a barbaric and pagan religion whose adherents were fanatically enthused. It also reveals the ambivalent stance that evangelicals in the early nineteenth century could adopt towards Islam, a doctrine which is presented as a necessary gateway religion from which Indians can gain access to Protestant Christianity. Furthermore, the article argues that the narrative was designed as an instrument that was intended to instantiate a transformation in the very mentalities of 'heathens', by displacing Hindu forms of religiosity and mental landscapes with Judeo-Christian text-based religious experience and imagery.